Accuracy of Achalasia Quality of Life and Eckardt scores for assessment of clinical improvement post treatment for achalasia. Issue 2 (1st September 2020) - Slone, Samuel; Kumar, Ambuj; Jacobs, John; Velanovich, Vic; Richter, Joel E
Abstract: Achalasia Quality of Life (ASQ) and Eckardt scores are two patient-reported instruments widely used to assess symptom severity in achalasia patients. ASQ is validated and reliable. Although Eckardt is commonly used, it has not been rigorously assessed for validity or reliability. This study aims to evaluate (i) the accuracy of Eckardt and ASQ for assessing improvement post-treatment (predictive validity), (ii) accuracy of Eckardt and ASQ for assessing improvement post-treatment with pneumatic dilatation (PD) versus surgical myotomy (predictive validity), and (iii) convergent validity of Eckardt and ASQ tools. Patients with achalasia treated between 2011 and 2018 were eligible. Both instruments were administered by telephone. Treatment failure was determined by the review of medical records by two clinicians. The predictive ability of ASQ and Eckardt instruments in identifying treatment successes and failures was determined using receiver operating characteristics analysis and summarized as area under the curve (AUC). A total of 106 patients met inclusion criteria with 39 PD, 51 Heller myotomy, and 16 per-oral endoscopic myotomy. A review of medical records and esophageal testing revealed 13 failures (12%). AUC for Eckardt was 0.96 (95% confidence interval [CI] 0.87–0.99] and ASQ 0.97 (95% CI 0.92–0.99). The Eckardt cutoff 4, and ASQ, cutoff 15, were 94% and 87% accurate in identifying treatment successes versus failures, respectively. The correlation coefficient between the two tools was 0.85. In conclusions, (i) ASQ and Eckardt scores are valid and reliable tools to assess symptom severity in achalasia patients, (ii) both instruments accurately classify treatment successes versus failures, and (iii) the choice of tool should be informed by the physicians and patients' values and preferences and repeat physiologic testing may be reserved for treatment failures with either instrument and patients classified, as treatment successes may be spared routine physiologic testing in the long term.